The application of a Strategic Human Resources Management model in the South African consumer goods industry - Monji, Lilian Clementina (My University, 2014)
In recent years, the trend of the South African consumer goods industry has shown a positive growth in sales volumes, mostly contributed by an increase in the middle income class level of middle-income class and increasing access to credit cards, resulting in the increasing purchasing power of consumers. However, for companies operating in this industry to benefit from the trend, they have to create ways to ensure they can compete successfully. Certainly, one such lever is for companies to strategically lock in their human resources as a source of competitive advantage over other firms. Against this background, the purpose of this research was to assess the application of the resource based view as the strategic human resources management model in the South African context. Drawing from data collected through semi structured interviews from a sample comprising of 14 senior HR practitioners, this report attempts to establish whether companies implement human resources management strategically using the theory of the resource based view (RBV) model. According to the theory of the RBV model, strategic implementation of human resources management occurs when companies have got policies in place for the studied strategic human resources management (SHRM) elements and the practices of the elements are in alignment with the organisation’s strategic objectives. The RBV SHRM elements explored in this research include; staffing, training, rewards and recognition, performance appraisal, employee participation and communication, and work design. The results of the research indicated that all interviewed companies practice staffing, training and performance appraisal elements strategically. Six companies practice rewards and recognition element strategically, five of the 14 interviewed companies practice employee participation and communication strategically and only three companies practice work design element strategically. Therefore of the 14 interviewed companies, only three companies apply the RBV tool as the strategic human resources management model. In summary the companies operating in the South African consumer goods industry hardly implement the RBV tool as the SHRM model. Therefore, it is recommended that companies have to apply all of the RBV elements as a SHRM model for them to compete successfully.
Keywords: Personnel management , Consumer goods -- South Africa